Sociodemographic factors affecting not receiving COVID-19 vaccine in Japan among people who originally intended to vaccinate: a prospective cohort study - Matsuyama, Akiko; Mori, Takahiro; Ogami, Akira; Mafune, Kosuke; Tateishi, Seiichiro; Kuwamura, Mami; Muramatsu, Keiji; Fujino, Yoshihisa; Mori, Koji; , CORoNaWork project (Frontiers in Public Health, 2023)
Objective Vaccine hesitancy is a major issue for acquiring herd immunity. However, some individuals may go unvaccinated owing to inhibitory factors other than vaccine hesitancy. If there is even a small number of such people, support is needed for equitable vaccine distribution and acquiring herd immunity. We investigated sociodemographic factors that affected not undergoing COVID-19 vaccination in Japan among individuals who had strong intention to vaccinate before beginning the vaccination. Methods We conducted this prospective cohort study on workers aged 20–65 years from December 2020 (baseline), to December 2021 using a self-administered questionnaire survey. There were 27,036 participants at baseline and 18,560 at follow-up. We included 6,955 participants who answered yes to this question at baseline: “Would you like to receive a COVID-19 vaccine as soon as it becomes available?” We applied multilevel logistic regression analyses to examine the association between sociodemographic factors and being unvaccinated at follow-up. Results In all, 289 participants (4.2%) went unvaccinated. The odds ratios (ORs) for being unvaccinated were significantly higher for participants aged 30–39 and 40–49 than those aged 60–65 years. Being divorced, widowed, or single, having low income, and having COVID-19 infection experience also had higher ORs. Discussion We found that some participants who initially had strong intention to vaccinate may have gone unvaccinated owing to vaccine side effects and the financial impact of absenteeism due to side effects. It is necessary to provide information repeatedly about the need for vaccination as well as social support to ensure that those who intend to vaccinate are able to do so when aiming for acquiring herd immunity through vaccination against COVID-19 as well as other potential infection pandemics in the future.